Fibroblast Growth Factor 19 Increases the Excitability of Pre-Motor Glutamatergic Dorsal Vagal Complex Neurons From Hyperglycemic Mice - Wean, Jordan B.; Smith, Bret N. (Frontiers in Endocrinology, 2021)
Intracerebroventricular administration of the protein hormone fibroblast growth factor 19 (FGF19) to the hindbrain produces potent antidiabetic effects in hyperglycemic mice that are likely mediated through a vagal parasympathetic mechanism. FGF19 increases the synaptic excitability of parasympathetic motor neurons in the dorsal motor nucleus of the vagus (DMV) from hyperglycemic, but not normoglycemic, mice but the source of this synaptic input is unknown. Neurons in the area postrema (AP) and nucleus tractus solitarius (NTS) express high levels FGF receptors and exert glutamatergic control over the DMV. This study tested the hypothesis that FGF19 increases glutamate release in the DMV by increasing the activity of glutamatergic AP and NTS neurons in hyperglycemic mice. Glutamate photoactivation experiments confirmed that FGF19 increases synaptic glutamate release from AP and NTS that connect to the DMV in hyperglycemic, but not normoglycemic mice. Contrary to expectations, FGF19 produced a mixed effect on intrinsic membrane properties in the NTS with a trend towards inhibition, suggesting that another mechanism was responsible for the observed effects on glutamate release in the DMV. Consistent with the hypothesis, FGF19 increased action potential-dependent glutamate release in the NTS in hyperglycemic mice only. Finally, glutamate photoactivation experiments confirmed that FGF19 increases the activity of glutamatergic AP neurons that project to the NTS in hyperglycemic mice. Together, these results support the hypothesis that FGF19 increases glutamate release from AP and NTS neurons that project to the DMV in hyperglycemic mice. FGF19 therefore modifies the local vago-vagal reflex circuitry at several points. Additionally, since the AP and NTS communicate with several other metabolic regulatory nuclei in the brain, FGF19 in the hindbrain may alter neuroendocrine and behavioral aspects of metabolism, in addition to changes in parasympathetic output.